2019
DOI: 10.1155/2019/7249679
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Male Reproductive Toxicity of Chinese Materia Medicas

Abstract: In recent years, as the infertility rate in China has been increasing year by year and semen quality decreasing, male reproductive toxicity of drugs attracts more and more attention. There are many factors that cause male reproductive toxicity, among which Chinese materia medica is an important aspect. This article will introduce the male reproductive toxicity of Chinese materia medicas grouped by different effectivenesses such as immunosuppressant, evacuant, diuretic, cardiotonic, anti-infective drug and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…It is known that glycosides, like ginsenosides, have multiple pharmacologic effects, such as anti‐tumour, anti‐fatigue, anti‐ageing and enhanced immunity. However, ginsenosides GRg1 and Rb3 of P. ginseng may result in growth retardation and dyszoospermia, respectively (Li, Li, et al, 2019; Liu et al, 2006). According to the literature, dangerous compounds of herbs, such as Carpesii Fructus , Sparganii Rhizoma and Rhizoma Pinelliae , that induce reproductive toxicity remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that glycosides, like ginsenosides, have multiple pharmacologic effects, such as anti‐tumour, anti‐fatigue, anti‐ageing and enhanced immunity. However, ginsenosides GRg1 and Rb3 of P. ginseng may result in growth retardation and dyszoospermia, respectively (Li, Li, et al, 2019; Liu et al, 2006). According to the literature, dangerous compounds of herbs, such as Carpesii Fructus , Sparganii Rhizoma and Rhizoma Pinelliae , that induce reproductive toxicity remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(Chan, 2011, 2015; Yang et al, 2021). Additionally, reduction of male testosterone secretion and deterioration of secondary sexual characteristics have been observed after long‐term exposure to morphine which is also a risk substance of Papaveraceae (Li, Li, et al, 2019).…”
Section: Classification On the Risk Components In Tcm‐induced Reprodu...mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In a long-term clinical observation, it has been found that reproductive issues associated with herbal therapies have increased recently, especially in patients with autoimmune disorders and cancer. [3] Triptolide (TP) is a major active ingredient of Tripterygium wilfordii Hook F, [4] which exhibits various biological functions, including immunosuppression, [5] antitumor activity, [6] antiinflammatory, [7] neurotrophic, and neuroprotective effects. [8] However, TP has many side effects that can cause damage to multiple organs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] In a long-term clinical observation, it has been found that reproductive issues associated with herbal therapies have increased recently, especially in patients with autoimmune disorders and cancer. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%